Comparison of echocardiographic parameters of amputee football players with active football players and sedentary individuals - Kurtoglu, A.; Kurtoglu, E.; Konar, N.; Çar, B.; Eken, Ö.; Prieto-González, P.; Nobari, H. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background The purpose of this study is to compare the echocardiographic (ECHO) parameters of amputee football players (AF) with those of athletes without a disability (football players) (FP), and sedentary individuals (SI).